Fruiting of new blueberry cultivars introduced in Belarus - Drozd, Olga V. (Experimental Biology and Biotechnology, 2023)
Based on long-term studies of 15 cultivars of highbush blueberry and 1 cultivar of lowbush blueberry, introduced in Belarus, the peculiarities of entering the stages of generative development and industrial fruiting, yield, fruiting frequency are shown. It has been established that blueberry plants enter the generative phase of development at the age of 4 years, and the stage of industrial fruiting at the age of 6 years. Average yield 2.0 kg per plant and more in the conditions of Belarusian Polesie was noted in highbush blueberry cultivars Goldtraube, Sunrise, Collins, Bluecrop, Bluejay, Denise Blue and Spartan. The cultivars Bluecrop, Spartan, Putte, Bluejay, Brigitta Blue, Sunrise, Toro, Bonus, Puru, Collins and Denise Blue are characterised by more regular fruiting.